Effectiveness of collaborative and demonstration methods of teaching in advancing students’ achievement and retention in chemistry - Abbey-Kalio, Ibiyengibo (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2023)
This paper examined the effectiveness of collaborative and demonstration methods of teaching senior secondary school students’ academic achievement and retention in chemistry. A quasi-experiment (non-randomized pretest-posttest control group) design was adopted for the study. The study comprised 114 chemistry students drawn from two different private senior secondary schools in Port Harcourt Local Government Area in Rivers State. A purposive sampling technique was used to select the two schools into experimental and control groups. Students were tested in their real-class situation, whereby the experimental group was taught using the collaborative method and the control group was taught using the demonstration method. Both groups were subjected to a pretest and after the teaching, to a posttest. The test questions were drawn from the class scheme of work. The instrument chemistry achievement test (CAT) was validated and the Cronbach Alpha method was used to determine the reliability coefficient as 0.7. Data analysis was done using means and standard deviations for the research questions while analysis of variance (ANOVA) was used for testing the research hypotheses at 0.05 level of significance. The findings of the study revealed that the collaboration method of teaching enhanced both academic achievement and retention in chemistry students more than the demonstration method of teaching. Furthermore, female chemistry students' academic achievement and retention enhanced better than their male counterparts. Based on the findings, several recommendations were made which include that curriculum developers should see the need to integrate a variety of innovative teaching strategies in the teaching-learning process as recommended by global standard practices.